Genetic divergence and resistance of sugarcane genotypes to Diatraea saccharalis - Tomaz, Adriano Cirino (2014)
The sugarcane stalk borer Diatraea saccharalis Fab. (Lepidoptera: Crambidae) is the most important pest of sugarcane in Brazil. However, despite the importance of this pest, there is a lack of efficient methods to compare the resistance of genotypes and select resistant sugarcane genotypes to be employed by sugarcane breeding programs. This study was conducted to determine a greenhouse method to compare stalk damage among sugarcane genotypes, investigate resistance factors present in the leaves, stalk surface and within the stalks of six Brazilian sugarcane cultivars and the relationship among these resistance factors. In addition, we assessed the genetic divergence of sugarcane genotypes to borer resistance by using cluster analysis. The infestation of 7- month-old single plants with 20 larvae (3rd - 4th instar) per plant for assessment of tunnel length was proved adequate to compare stalk damage among sugarcane genotypes. The genotypes SP803280, RB928064 and RB835486 had the lowest stalk damage while SP891115 had the highest damage. The larvae spent more time to enter the stalk of the genotype SP803280 compared to SP891115, indicating that this genotype has some resistance trait in stalk surface delaying the larvae entrance in the stalk. Late-stages larvae feeding in the stalk of SP813250 had the lowest weight gain indicating that this genotype present some resistance factor affecting larval development within the stalks. Correlation analysis among resistance factors indicated that the time spent by larvae to enter the stalk is more related to stalk damage than the larval feeding within the stalks. The genotypes RB867515 and SP891115 caused the highest mortality of early-stage larvae feeding on the leaves, which indicate the presence of antibiotic factors in the leaves of these genotypes. Cluster analysis divided the genotypes in three groups, indicating the genetic dissimilarity between genotypes. The results from this study may contribute in selection of resistant clones and choice of genitors for crossings in sugarcane breeding programs.